Supply Chain Characteristics that Impact on Forms of Collaborative Planning - Huang, Jie Hong (2008)
There has been an increasing recognition of the importance of supply chain planning, especially collaborative planning. Unfortunately, few operational and standard guidelines have been developed in the development of collaborative planning. This dissertation is intended to develop a new operational framework of collaborative planning within the high-technology business sector by the method of case studies. Through the analysis of nine case studies of collaboration whose central firms operate in electronic, automotive and aerospace sectors separately, eight critical factors of supply chain characteristics (i.e. supply chain strategy, product characteristics, supply network, uncertainty, information, interdependence, power, technology) that impact on the forms of collaborative planning have been examined. Furthermore, a new framework of collaborative planning in six business processes horizontally with five developing procedures vertically has been developed within the high-technology business sector. From the theoretical value, this framework provides a foundation for further research to identify other collaborative elements and planning forms in each business sector. From the practical value, it can enable firms to find out related issues and collaborative planning steps to develop seamless relationship. But flexible adjustment of this framework according to the specific supply chain characteristics is essential during implementation.